Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173868
|View full text |Cite
|
Sign up to set email alerts
|

Juxtapeer

Abstract: Figure 1. The review interface presents two peer submissions side-by-side, and aligns corresponding submission parts so reviewers can identify similarities and differences. To scaffold feedback, a rubric guides the reviewer through a structured comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A review of 51 studies [21] identified the main domains that have leveraged crowdsourcing: to generate content, provide training experiences, exchange knowledge, and gather feedback from other experts and novices [10,12,20]. Researchers have developed systems to crowdsource grades, provide feedback on student work, and increase student knowledge attainment as they assess their own or peers' work [6,10,13,33]. However, most of these cases occur in self-contained courses where students assess each other, often in higher education settings, and where students can be expected to have some domain knowledge.…”
Section: Crowdsourcing Systems In Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of 51 studies [21] identified the main domains that have leveraged crowdsourcing: to generate content, provide training experiences, exchange knowledge, and gather feedback from other experts and novices [10,12,20]. Researchers have developed systems to crowdsource grades, provide feedback on student work, and increase student knowledge attainment as they assess their own or peers' work [6,10,13,33]. However, most of these cases occur in self-contained courses where students assess each other, often in higher education settings, and where students can be expected to have some domain knowledge.…”
Section: Crowdsourcing Systems In Educationmentioning
confidence: 99%
“…A key issue in educational crowdsourcing is how to increase the overall quality of the work [6,10,14,26]. Educational crowdsourcing tasks often require specialized knowledge (e.g., teaching and learning knowledge, or skills to assess a given assignment) that cannot be solved effectively by unskilled crowdworkers [24].…”
Section: Crowdsourcing Systems In Educationmentioning
confidence: 99%
See 2 more Smart Citations